Myocardial revascularisation in patients with severe left ventricular dysfunction. Early and midterm results - Skorpil, Jirí; Brát, Radim; Docekal, Bohumil; Motyka, Oldrich (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2004)
AIMS: This retrospective study evaluates early and midterm results in patients with severe left ventricular dysfunction. TECHNIQUE: Ninety-seven consecutive patients with coronary artery disease and ejection fraction of left ventricle (LVEF) less or equal to 25 % underwent elective coronary artery bypass graft procedure between September 1998 and December 2001. Mean age at operation was 66 (47-86) years. The main symptoms were angina class III-IV Canadian Cardiovascular Society (CCS) in 78 patients (80 %) and dyspnoea class III-IV New York Heart Association (NYHA) in 43 patients (44 %). The major indications for surgery were severe angina, dyspnoea in 90 patients (93 %). Cardiac index (CI), echocardiography (ECHO), planimetry, end-diastolic pressure of left ventricle (LVEDP), end-diastolic diameter of left ventricle (LVEDd) were used to access left ventricular function preoperatively. ECHO was also used to access left ventricular function postoperatively. RESULTS: Early postoperative (30 days) mortality was 4.1 %. Complications had 25 patients (26 %) postoperatively. Two years survival was 95.7 %. Class III-IV CCS and/or NYHA had 17 patients (17.5 %) two years after surgery. LVEF (assessed by ECHO) improved from 23.1 % preoperatively to 36.0 % postoperatively (p < 0.05). CONCLUSION: The study showed that elective myocardial revascularisation in patients with severe left ventricular dysfunction and signs of myocardial viability is not necessarily associated with high operative mortality. It can be performed safely with respectable midterm survival in concordance with left ventricular function improvement, symptom relief and quality of life improvement.
Keywords: Postoperative Complications; senioři; Aged; dysfunkce levé srdeční komory; Male; lidé; lidé středního věku; Humans; míra přežití; Ventricular Dysfunction, Left; Middle Aged; Survival Rate; Coronary Artery Bypass; senioři nad 80 let; Aged, 80 and over; koronární nemoc; Coronary Disease; mužské pohlaví; koronární bypass; pooperační komplikace; ženské pohlaví; Female